2008
DOI: 10.1889/1.3069718
|View full text |Cite
|
Sign up to set email alerts
|

37.1: Novel Development of Large‐Sized Electrowetting Display

Abstract: A large size panel manufacturing process for electrowetting display (EWD) by using surface treatment and ink‐jet printing (IJP) techniques had been developed. for hydrophilic rib fabrication, surface treatment technique was adopted to reinforce the adhesion of hydrophilic material on hydrophobic layer to achieve large‐Sized panel manufacturing. Also, for dosing of non‐polar liquid, IJP technique was used to dose the liquid into the unit pixel individually. By using IJP technique to dose the red, green, and blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…The degree of oil contraction is very small, while the voltage is below the threshold, and apparent contraction can only be observed while the applied voltage is higher than the threshold . 11 Previous research found that dyed oils may reduce their astringency even if the applied voltage was maintained. 12,13 This phenomenon is called "backflow."…”
Section: Electrowetting Display Driving Principlementioning
confidence: 99%
“…The degree of oil contraction is very small, while the voltage is below the threshold, and apparent contraction can only be observed while the applied voltage is higher than the threshold . 11 Previous research found that dyed oils may reduce their astringency even if the applied voltage was maintained. 12,13 This phenomenon is called "backflow."…”
Section: Electrowetting Display Driving Principlementioning
confidence: 99%
“…1 This so-called dynamic boundary condition results in the adjustment of the curvature of the surface near the wall. If w is the contact angle at the wall, then the surface normal at the live cell next to the wall is (6) where and are the unit vectors normal and tangential to the wall, respectively. The combination of this contact angle with the normally calculated surface normal one cell away from the wall determined the local curvature of the surface, and this curvature is used to adjust the body force term in the surface-tension calculation.…”
Section: Experiments 2: Simulation Theoretical Modelmentioning
confidence: 99%
“…Several ink-jet-printing (IJP) technologies were applied to the EWD and preceded fabrication. 6,7 IJP is an emerging technology that makes use of drop-on-demand technology (a similar printing technology). It can be used in a large-area manufacturing process that includes precise traces or drops, fast production, dispensing, and coating.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many different technologies have been proposed for use in reflective displays [1][2][3][4]. One of the emerging technologies is the electrowetting due to its high contrast ratio, video speed, and low power consumption [3][4][5][6][7]. EWD was first proposed by Hayes and Feenstra by manipulating the movement of the colored oil film with the applied varying voltage [3].…”
Section: Introductionmentioning
confidence: 99%
“…EWD was first proposed by Hayes and Feenstra by manipulating the movement of the colored oil film with the applied varying voltage [3]. For full color EWD, 1-layer and 3-layer architectures were proposed [4][5].…”
Section: Introductionmentioning
confidence: 99%